The Evaluation of Medicolegal Autopsy Events which was Done in Elazığ Between 2001-2006 - Tokdemir, Mehmet; Türkoğlu, Abdurrahim; Kafadar, Hüseyin; Düzer, Selma (The Bulletin of Legal Medicine, 2008)
Suspicious and not natural all deaths are evaluated as medicolegal death event. Autopsy is an application to determine the death reason and to adduce material proofs at the end of accident, suicide, murder, unexpected death events or the death when the person was alone,because of preventig some problems in the future resulting from medicolegal positions. In this study, we aimed to evaluate the autopsies which was done in our city according to age, sex, death reason, origin and the variation of these as to the years. We also aimed to make a comparison with the other cities data. Between 2001- 2006, 679 events were sent from Elazığ city center, periphery cities and the districts. This 679 events whose dead examinations and autopsies were done by Department of Forensic Medicine of Fırat Medical Center and Branch Office Manager of Forensic Medicine were examined as retrospectively according to the age, sex, origin and death reason. 91 (13.4%) dead examination events of total 679 events and 6 (1.02%) events can't be fixed the death reason in 588 events whose autopsies were done were excepted from our study. It is fixed that the examined 582 events included 431 men (74.1 %), 151 women (25.9 %), the youngest is 1, the oldest is 101 and the avarage age is 36.9 + 21.9. The accident is cammonly seen as origin (36.9%) and suicide, murder, death from natural reasons and terror canflicts follow this. 475 of the events (81.6 %) died from unnatural reasons and 107 of the events (18.4 %) died from natural reasons. Where as the firearm wounds are the first in the unnatural death reasons, the cardiovascular diseases are the first in the natural death reasons. Medicolegal autopsy events which were done in our city show similar features with the other cıtıes' studıes in terms of numerical increase in the years,age,sex,origin and death reasons. Because of terror events our area has a difference from the other cities and so in terms of origin we included the death events of terror acts into the our study. Firearm wounds being the first reason in the unnatural deaths show unsufficiency in the medical examination of having firearm and legal controls. For this reason, it is important that authorized persons must be more careful in the procedures of licensing of having arm.Keywords: Forensic medicine, autopsy, accident, murder, suicide
Keywords: forensic medicine; autopsy; accident; murder; suicide